دور العقل في التجديد الدعوي :دراسة تحليلية (Al-Qamar, 2024)
The Intellect is Allah’s (SW) greatest blessing, and like every blessing in this world, it is also part of man’s examination paper. Rather, it is the fundamental part of every human being’s life. He who has no wisdom & intellect has no exam, and he who does not have a wisdom or intellect he/she is not subject to any kind of responsibility. Allah Almighty said: (And when it is said to them, “Follow what Allah has revealed,” they say, “Rather, we follow what we found our fathers upon, even though their fathers were void of wisdom and guidance”) This verse of holy Quran denounces those who have nullified their wisdom and followed their fathers in false beliefs that have no justified reason. Allah Almighty also said: (No soul can believe, except by the will of Allah. And He will place doubt (or obscurity) on those who will not understand). Yes, the key part in a person’s exam is his/her wisdom and intellect. A person’s body and money are linked to his/her work, and the mind is linked to faith. It is clear that faith precedes work, and both are indispensable to succeed, neither in this world nor in the afterlife. The basic point of the test paper is that there are two ways to solve it, either Right or wrong, and for this reason the paths to failure and success emerge from the same test. Allah Almighty said: (It is He who created death and life that He may test you which of you is best in deeds; and He is the Mighty, the Forgiving) ...The meaning of this verse is that Allah is the one who created death and life to test you and to know after the test which of you is righteous and which of you is not, and there is no way to salvation except by doing that in the correct manner. And Allah Almighty said: (So whoever is removed from the Fire and admitted to Paradise has already achieved success). Therefore, the use of the wisdom and intellect must be among the basic and indispensable tasks of life, and it should be used not only to meet some trivial needs, but for great purposes such as salvation, well-being, pride and dignity in this world and clear victory in the afterlife. The belief that modernity is based on bypassing the Sharia texts and denying them cannot be acceptable, because the desired modernity in dealing with the sharia texts means adhering to them completely, while reconsidering the human effort related to interpreting these texts. Because there has become an urgent need for the wisdom to play its effective and fruitful role in renewing the sciences and building civilization. By contemplating the Qur’anic texts calling for the mind’s mobility, its science, and its mission to advance Knowledge, development, walking in the land, and discovering what is new in it, the meditator finds that the role of the mind has become a major role in the fields of construction, progress, and contemporary civilization, and in the field of renewal, development, and giving. God said:God Almighty said: (Indeed, in the creation of the heavens and the earth, and the alternation of night and day, and the ships that sail in the sea for the benefit of people, and what God has sent down from the heaven... water and revives the earth therewith after its death, and scatters in it every living creature, the shifting of the winds, and the clouds subdued between the sky and the earth - these are signs for a people. Akloun). The verse stimulates the wisdom and intellect to think and contemplate the creation of the heavens and the earth, the difference between night and day, and the ships that move in the sea. So, given the importance of this topic, as a researcher I decided to write this research under the title “The Role of wisdom/intellect in Da’wah Renewal”. This research paper is divided into five sections, as follows:First Section: The wisdom does not oppose Alwahy or vice versaSecond Section: removing suspicionThird Section: The role of the wisdom in building civilizationFourth Section: The role of the wisdom in renewalFifth Section: Da’wah renewal
Keywords: wisdom; intellect; innovation; Dawah; and Da’wah renewal